O jornalismo imersivo no The New York Times: um estudo sobre a produção de notícias em 360 graus - Andrade, Thiago da Silva (2019)
This research proposes to study the immersive journalism through the analysis of pieces elaborated by The New York Times and to promote a theoretical reflection on the practices of production of audiovisual products. The change in consumer behavior has revolutionized the form of journalistic production and how contemporary man consumes information. Based on the theoretical contribution of authors like McLuhan, Biocca, Craig, Murray, among others, we infer that these audiovisual pieces productions aided by the new technologies have undergone changes. And they extended to the new means of consumption as Virtual Reality (VR), through videos 360 degrees, using headsets, such as glasses of VR. The research is of a bibliographic character, with exploratory and explanatory character. It is also configured as a case study. The corpus is made up of reports from the Daily 360 series, produced by the American newspaper The New York Times. We will analyze how the 360º video can promote the immersion of the viewer in the news narrative, favoring an interactive environment in immersive journalism.